Screening of chloroplast promoters for Hevea brasiliensis chloroplast transformation - Ag Ismail, Anas Akmal; Zainal Abidin, Zaima Azira; Zainuddin, Zarina (Universiti Teknologi Malaysia, 2015)
In recent years, the growth in the use of recombinant proteins has grown tremendously. With the aid of the advances in DNA recombinant biotechnology, molecular farming in plants has been applied to meet this increasing demand where plants have emerged as one of the most promising general production platforms for recombinant proteins. Hevea brasiliensis is one of the main commodities in Malaysia and widely cultivated species for commercial production of latex. This important plant has been used to express recombinant proteins such as a single-chain variable fragment (scFv) antibody against the coat protein of Streptococcus gordonii (an oral dental bacterium), human serum albumin and human atrial natriuretic. The genes that encodes for the recombinant proteins were targeted into the nucleus genome of Hevea but the proteins were expressed in low concentration. Generating transgenic plant using chloroplast transformation offers many advantages in comparison to nuclear transformation and many researches have been made to apply this strategy to enhance agronomic traits or produce recombinant protein in several plant species. Since chloroplast is highly polyploidy, it allows high-level foreign protein expression. Given the generally very high foreign protein accumulation rates that can be achieved in transgenic chloroplasts, the aim of this study is to screen a number of chosen endogenous Hevea chloroplast promoters to drive the expression of the reporter gene, uidA for Hevea specific chloroplast transformation vector. Three promoters were chosen for this experiment which are; rbcL, psbA and rrn16 promoters. The putative regions of these promoters were derived from the chloroplast genome sequence of Hevea. Analyses of the three putative promoter regions using multiple sequence alignment with comparable regions from other plant species show significant sequence homology. Further analyses of the putative regions using in-vitro transcription are planned for future study. It is hoped that with the development of an optimized expression vector will allow high expression of valuable recombinant protein in the chloroplast of Hevea. Keywords: Hevea brasiliensis, chloroplast transformation vector, promoter, rbcL, psbA, rrn16 ©